THE INFLUENCE OF THE WHISTLEBLOWING SYSTEM, INDIVIDUAL MORALITY AND CULTURE ORGANIZATION AGAINST FRAUD PREVENTION - Putu Aprilia Wulandari; Made Yenni Latrini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The purpose of this research is to determine the influence of the whistleblowing system, individual morality and organizational culture in preventing fraud. This research was carried out at PT. Development Bank The Bali Klungkung branch used 45 samples as respondents and used a purposive sampling approach to select samples. Multiple linear regression analysis techniques with the help of SPSS were used in this research. The findings in this research explain that the whistleblowing system, individual morality and organizational culture have a positive influence on preventing fraud at PT. Bali Regional Development Bank Klungkung branch.